Protein release studies from biodegradable polymers - Goh, Brenda Hui Ling. (2009)
With the breakthrough invention of biodegradable sutures in the 1960s, biodegradable polymers have received immense focus for drug delivery applications in biomedical field since then. In order for a material to be successfully used in controlled drug delivery systems, the important criteria includes being chemically inert with no leachable impurities and be readily processable. Polylactides and polyglycolides were used as absorbable suture material initially and as a result, further advancements were made to work with these polymers in controlled drug delivery systems. With these two parent homopolymers, a newly synthesized polymer, poly(lactide-co-glycolide) (PLGA) was introduced in the industry. In this report, release kinetics of solution-cast films of lysozyme loadings in PLGA as well as poly(ethylene oxide) (PEO) incorporated PLGA matrices were studied. The primary mechanisms observed from the release profiles were the burst effect of protein molecules, degradation-dependent relaxation of the polymer chains (increasing the free volume available for drug dissolution and release) and diffusional drug release. The incorporation of PEO further enhances the rate of solvent uptake and hydrolytic degradation of the polymer to accelerate the drug release. The profiles were substantiated and supported with fine analysis and interpretation of the experimental data, tabulation of figures and characterization of the surface morphology of the films at different point of degradation with the use of the scanning electron microscopy (SEM).